Association between Family Support and Depression Among Elderly Patients with Type 2 Diabetes Mellitus at Samarinda City Public Health Center - Fatimah, Farah Aini; Nugroho, Hary; Nugrahayu, Eka Yuni (Fakultas Kedokteran, 2024)
Diabetes mellitus (DM) is a metabolic disorder in carbohydrate, lipid and protein characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Elderly people with DM are very susceptible to depression. Depression can worsen the medical condition of people with DM. Family Support is one of the factors that can influence the depression status in elderly DM patients. The purpose of this study was to determine the relationship between family support and the level of depression in older people with type 2 DM at the Samarinda City Public Health Center. This was an analytical observational research design with a cross-sectional survey approach on three public health centers in Samarinda City. Two research instruments were used such as the Family APGAR questionnaire and the Geriatric Depression Scale (GDS) form, with topics of family support and elderly depression respectively. Sampling was done by purposive sampling technique and obtained 68 respondents. The results showed that 45 respondents (66,2%) perceive